Technique and timing in the womens forward two and one half somersault pike and mens three and one half somersault pike 3m springboard dives - Sanders, R. H.; Gibson, B. J. (Journal of Science and Medicine in Sport, 2000)
The purpose of this study was to compare the forward two and one half somersault dive in a pike position (105B) performed by females (n=25) and the forward three and one half somersault dive in a pike position (107B) performed by males (n=25) to determine changes required by females to successfully perform 107B. Video data of the dives performed at the 1999 FINA World Diving Cup were captured and digitised to obtain times and postures of the divers at specific events including hurdle landing, takeoff, and entry. Estimates of hurdle flight height and mass-normalised work done on the springboard were obtained from hurdle and flight times. Females performing 105B had significantly less hip and knee flexion at landing from the hurdle than males performing 107B. It is known from simulations that the ability to land in a very flexed position without absorbing energy depends on the ability to generate large extension torques at landing. Therefore, it is likely that females need to increase strength to successfully complete 107B.